Kualitas Layanan terhadap Kepuasan Pelanggan - Fausi Nurrahman; Abadi Sanosra; Ahmad Izzudin (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine and analyze the effect of service quality (tangible, reliability, responsiveness, assurance, and empathy) on customer satisfaction at the Hans Sukowono Workshop, where the Hans Sukowono Workshop is experiencing fluctuations in the number of visitors in 2020. This research method is a research study. quantitative descriptive. The population in this study are consumers or customers of the Hans Sukowono Workshop. The sample used is 100 respondents. The analysis tool uses multiple linear regression. The results showed, the results of the t test showed that, a) the tangible variable (X1) with a t count of 1.356 and a significance level of 0.038; b) variable reliability (X2) with t count of 1.105 and a significance level of 0.032; c) the responsiveness variable (X3) with t count of 3.360 and a significance level of 0.001; d) assurance variable (X4) with t count of 4.572 and a significance level of 0.000; e) Empathy variable (X5) with t count of 2.250 and a significance level of 0.027. In conclusion, service quality (tangible, reliability, responsiveness, assurance, and empathy) has a significant partial and simultaneous effect on customer satisfaction at the Hans Sukowono Workshop. Keywords: Service Quality (Tangibel, Reliabity, Responsiviness, Assurance, and Empathy), Customer Satisfaction